Explicit tests of palaeodrainage connections of southeastern North America and the historical biogeography of Orangethroat Darters (Percidae: Etheostoma: Ceasia). Issue 21 (7th October 2013) - Bossu, Christen M.; Beaulieu, Jeremy M.; Ceas, Patrick A.; Near, Thomas J.
Abstract The alteration in palaeodrainage river connections has shaped patterns of speciation, genetic diversity and the geographical distribution of the species‐rich freshwater fauna of North America. The integration of ancestral range reconstruction methods and divergence time estimates provides an opportunity to infer palaeodrainage connectivity and test alternative palaeodrainage hypotheses. Members of the Orangethroat Darter clade, Ceasia, are endemic to southeastern North America and occur north and south of the Pleistocene glacial front, a distributional pattern that makes this clade of closely related species an ideal system to investigate the number and location of glacial refugia and compare alternative hypotheses regarding the proposed evolution of the Teays‐Mahomet palaeodrainage. This study utilized time‐calibrated mitochondrial and nuclear gene phylogenies and present‐day geographical distributions to investigate hypothesized Teays‐Mahomet River connections through time using a dispersal–extinction–cladogenesis (DEC) framework. Results of DEC ancestral area reconstructions indicate that the Teays‐Mahomet River was a key dispersal route between disjunct highland regions connecting the Mississippi River tributaries to the Old‐Ohio Drainage minimally at two separate occasions during the Pleistocene. There was a dynamic interplay between palaeodrainage connections through time and postglacial range expansion from three glacial refugia that shaped the current genetic structure and geographical distributions of the species that comprise Ceasia.